Lost in the maze? Husserl, Ortega and Gaos facing the challenges of cultural diversity - Yazid Hisyam (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2020)
This article tries to show the way in which three prominent 20th century philosophers –– Edmund Husserl, José Ortega y Gasset and José Gaos–– have dealt with cultural diversity. Linked to each other by strong intellectual ties, the protagonists of the text propose three different ways of approaching this crucial and thorny issue in which the role assigned to reason is of special relevance. Husserl will trust her fully. Ortega, even the most Husserlian Ortega, will considerably lower such claims. And Gaos, radicalizing the perspectivist theses of his teacher, will consider that it is better to assume his impotence. The set of mirrors that the essay intends to create with the intersection of the three proposals aims to highlight the relevance of the philosophy made in Spanish in the most pressing debates of the present.